Compulsory collection of taxes and fees: some issues of competence - Nikanava, Nataliya N. (Journal of the Belarusian State University. Law, 2024)
In the Republic of Belarus, a decentralised system of enforcement is implemented, which is particularly expressed in the fact that a number of bodies are vested with powers to enforce the collection of taxes and penalties on them. Their competence is regulated by various legal acts, the provisions of which are not fully consistent with each other. The author of the article analyses the provisions on the competence of various bodies to collect taxes and penalties on them, as well as special rules for foreclosure on the property of taxpayers. The author believes that a decentralised system presupposes the consistency of the procedure for the enforcement of obligations arising from legal relations of the same legal nature, carried out by various bodies. However, in the Republic of Belarus, the rules that tax authorities, enforcement agencies and the Department for humanitarian activities of the Office of the President of the Republic of Belarus are guided by are characterised by significant differences, primarily in provisions on guarantees of the debtor’s rights. The author proposes changes to the legislation aimed at eliminating the overlapping jurisdictions of the above-mentioned bodies in collecting taxes, fees, and penalties on them.